Does the Strawberry Generation Have a Religiosity That Impacts Social Resilience? - Devi, Auriza Satifa (Universitas Islam Negeri Raden Intan Lampung, 2024)
The Strawberry Generation is a generation that is innovative, creative and has brilliant ideas but has a character that is easily fragile when receiving social pressure and has low social resilience abilities. Strawberry Generation refers to the age of the late millennial generation to the early Generation Z. The influencing factors are self-efficacy, self-esteem, optimism, social support, and level of religiosity. The Strawberry Generation can survive and rise from adversity by having social resilience. The aim of this research is to find out that religiosity has an impact on social resilience among Strawberry Generation students at SMK N 6 Surakarta. This research is quantitative correlational research. This research was conducted at SMK N 6 Surakarta with a total sample of 218 students from classes X and XI who were selected using accidental sampling. Data were collected using a religiosity scale (38 items with α 0.930) and a social resilience scale (36 items with α 0.958). Using content validity test with Aiken's V coefficient. Assumption tests are carried out using normality tests and reliability tests. Hypothesis testing using product moment correlation assisted with SPSS Version 25. The results of this research are that religiosity has an impact on social resilience with a correlation coefficient of 0.578 with a significance level of 0.000 (p<0.05) which shows that there is a positive relationship between religiosity and social resilience. This means that the higher the religiosity, the higher the social resilience of students and vice versa. The conclusion in this research is that H0 is accepted and Ha is rejected. The implication of this research is that religiosity can be a predictor in increasing social resilience in Strawberry Generation students at SMK N 6 Surakarta. Keywords: Religiosity; Social Resilience; Strawberry Generation